Nocardiopsis sp. SD5: A potent feather degrading rare actinobacterium isolated from feather waste in Tamil Nadu, India. (17th July 2013) - Saha, Subhasish; Dhanasekaran, D.; Shanmugapriya, S.; Latha, S.
<x xml:space="preserve">Abstract</x> Feather waste, generated in large quantities as a byproduct of commercial poultry processing, is nearly pure keratin protein, and keratin in its native state is not degradable by common proteolytic enzymes. The aim of the study was to find a potent feather degrading actinobacteria from feather waste soil. Out of 91 actinobacterial isolates recorded from feather waste soil in Tiruchirappalli and Nammakkal District, Tamil Nadu, India, isolate SD5 was selected for characterization because it exhibited significant keratinolytic activity. On the basis of the phenotypic, biochemical characterization and 16S rRNA gene‐sequencing studies, the isolate was identified as Nocardiopsis sp. SD5. Protease and keratinase activity of Nocardiopsis sp. SD5 were analyzed. The enzyme was more stable over the neutral pH and the temperature of 40 °C. The optimum temperature and pH for both proteolytic and keratinolytic activity was determined at 50 °C and pH 9, respectively. Enzyme inhibitors, detergents and chelator declined the enzyme activity with increasing concentration. Nondenaturing polyacrylamide gel electrophoresis and zymogram elucidated the presence of 30 and 60 kDa protease enzymes. These findings indicated that thermo alkaliphilic feather degrading strain Nocardiopsis sp. SD5 could be used to control the feather waste pollution and to convert keratin rich feather waste into useful feedstock for poultry industry.